Pemberdayaan Teman Sebaya untuk Strategi Regulasi Emosi, Pencegahan Perilaku Berisiko, dan Pemahaman Kesehatan Reproduksi Remaja - Vita Camellia; Khairunnisa Khairunnisa; Muhammad Ichwan; Farah Dhiba; Zulfendri Zulfendri; Dewi Gita (LPkM Universitas Bakrie, 2026)
Achieving the goals of Indonesia Emas 2045 requires a high-quality generation that is productive, innovative, capable of building harmonious social relationships, possesses strong character, and demonstrates awareness of the relationship between humans and environmental sustainability. In line with the programs of the Tebing Tinggi Population Control and Family Planning Office, the Forum Genre and the Youth Information and Counseling Center (Pusat Informasi dan Konseling Remaja [PIK-R]) have implemented youth empowerment activities to prevent drug abuse and early marriage. Findings from the Focus Group Discussion (FGD) indicated that adolescents had limited knowledge of emotion regulation strategies and reproductive health and had never received related training. This condition became the basis for implementing this community service program. The program was conducted over two days. On the first day, 67 students from several public senior high schools participated in emotion dysregulation screening using the Emotion Regulation Questionnaire (ERQ), psychological distress screening using the Kessler Psychological Distress Scale (K10), and educational sessions on emotion regulation and reproductive health. On the second day, 33 female students who were members of the Forum Genre and PIK-R participated in training on identifying cognitive distortions and practicing mindfulness. The results showed that 38.81% of participants did not experience psychological distress, while the remainder experienced mild to severe psychological distress. In addition, 25 participants (37.31%) predominantly used cognitive reappraisal, whereas 42 participants (62.69%) predominantly used expressive suppression. Overall evaluation revealed high participant satisfaction, participants expressing their readiness to apply and disseminate the knowledge to their peers.